Between Worship and Bribery: Charity in the Shadow of Electoral Politics - Awaluddin, Syah; Tjiptabudy, Jantje; Latupono, Barzah; Alfons, Sartje Sarah (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This article examines the blurred boundary between genuine ṣadaqah (charitable giving) and covert vote-buying during Indonesia’s 2024 general elections, offering an Islamic legal analysis grounded in the concepts of niyyah (intention), ikhlāṣ (sincerity), riyāʾ (ostentation), and evidentiary principles such as qarīnah (contextual indicators). While political actors often disguise electoral incentives as acts of worship, Islamic jurisprudence provides a normative framework to distinguish between sincere charity and manipulative political strategy. The study adopts a normative-juridical approach, combining descriptive-qualitative analysis with both classical Islamic sources, such as the Qur’an, Hadith, fiqh, and tafsir, and contemporary legal regulations, particularly Law No. 7 of 2017 concerning Elections. Data were collected through library research and analysed thematically using Islamic legal reasoning, legal maxims, and selected case illustrations from the 2024 elections. This methodological framework enables a nuanced interpretation of intention in Islamic law—not based on verbal confession but inferred through circumstantial and behavioural indicators. The main contribution of this research lies in its articulation of an evidentiary model rooted in Islamic jurisprudence (fiqh)—a structured framework for evaluating the ethical and legal status of charitable acts in politicised contexts based on indicators recognised in Islamic legal thought. This model equips scholars, regulators, and the public with the tools to detect and assess electoral misconduct disguised as religious virtue. This study presents a clear novelty in the form of a matrix of legal indicators—derived from Islamic legal ethics—as an original analytical tool to objectively evaluate political intent in charitable acts during elections. By integrating classical Islamic thought with contemporary electoral challenges, this article contributes a unique perspective to Islamic legal studies and democratic governance, laying the groundwork for a reformed jurisprudential approach to political ethics in Muslim-majority societies.